Exploring the Link Between Allergies and Neurological Diseases: Unveiling the Hidden Connections - Kamila Saramak (Allergies, 2025)
The interplay between allergic diseases and neurological disorders has gained increasing attention over the past decades, highlighting potential shared pathophysiological pathways. Allergic diseases, including asthma, eczema, and allergic rhinitis, are characterized by chronic inflammation and immune dysregulation, which may impact the pathogenesis of certain neurological conditions. Emerging evidence suggests that conditions such as multiple sclerosis (MS), migraine, epilepsy, neurodegenerative diseases, and neurodevelopmental disorders may be influenced by systemic inflammation and altered immune responses associated with allergies. The purpose of this paper is to provide an overview of current epidemiological evidence suggesting a relationship between allergic and neurological diseases. Understanding the complex interactions between allergic and neurological diseases could provide new insights into their aetiology and reveal novel therapeutic targets, paving the way for integrated approaches in managing comorbid allergic and neurological conditions, ultimately improving patient outcomes and quality of life.